Including a Symposium on Albert O. Hirschman - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo; Bianchi, Marina, 1947-; Franzini, M. (Maurizio), 1950- (Research in the history of economic thought and methodology ;, 2016)
The Research in the History of Economic Methodology (RHETM) 34B, includes original research from preeminent scholars in the field. RHETM is one of the oldest and most respected publications in the field, and the Vol 34B is crucial for economists, methodologists, and historians of the social sciences.